1986
DOI: 10.1128/jcm.24.4.573-580.1986
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of antigenic variation among rabies virus isolates by using monoclonal antibodies to nucleocapsid proteins

Abstract: Rabies virus isolates from terrestrial animals in six areas of the United States were examined with a panel of monoclonal antibodies to nucleocapsid proteins. Characteristic differences in immunofluorescence reactions permitted the formation of four antigenically distinct reaction groups from the 231 isolates tested. The geographic distribution of these groups corresponded well with separate rabies enzootic areas recognized by surveillance of sylvatic rabies in the United States. Distinctive reaction patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
3

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(19 citation statements)
references
References 11 publications
0
16
0
3
Order By: Relevance
“…have delineated antigenic patterns in both the USA and Canada (Smith et al 1986;Webster et al 1 986), classified rabies strains in Canada into four major groups (Fiamand et al 1980a;Webster et al 1986), and confirmed vaccine-induced disease when an attenuated vaccine reverted to virulence (Whetstone et al 1984). The discovery of a marker of virulence as recognized by a particular monoclonal antibody would be important for identification of potential epizootics and would facilitate new vaccine production.…”
Section: Discussionmentioning
confidence: 99%
“…have delineated antigenic patterns in both the USA and Canada (Smith et al 1986;Webster et al 1 986), classified rabies strains in Canada into four major groups (Fiamand et al 1980a;Webster et al 1986), and confirmed vaccine-induced disease when an attenuated vaccine reverted to virulence (Whetstone et al 1984). The discovery of a marker of virulence as recognized by a particular monoclonal antibody would be important for identification of potential epizootics and would facilitate new vaccine production.…”
Section: Discussionmentioning
confidence: 99%
“…Rabies virus belongs to the genus Lyssavirus in the family Rhabdovirus and causes an acute fatal encephalomyelitis in an extremely broad host range of mammals. Red pandas have been diagnosed with rabies virus infection, and rabies virus has been isolated from red pandas [56]. Clinical signs are not definitive or species-specific beyond acute behavioural alterations.…”
Section: Rabies Virusmentioning
confidence: 99%
“…In several studies, the antigenic organization of rabies virus N protein has been defined by the use of monoclonal antibodies (MAbs) (3,9,13,14,16 Slides were stored at -30 C until needed. Reactivity of MAbs to various rabies and rabies-related viruses in IFA was determined with FITCconjugated goat antibodies against mouse immunoglobulins (ICN, U.S.A.) as described previously (12).…”
mentioning
confidence: 99%